Introduction to eco-efficient masonry bricks and blocks - Pacheco-Torgal, F. (2015)
Although masonry units have been used for several millennia they still are and will continue to be widely used construction materials around the world. This chapter provides brief historical facts on masonry bricks and blocks. Brick production data of several countries is included. The contributions of these materials for eco-efficient construction are described. This chapter includes the contribution for the reduction of heat energy needs for buildings, the reduction of embodied energy and also the production of masonry bricks and blocks with the incorporation of industrial wastes. An outline of the book is included.